Quantification of serum elastase inhibitory activity in patients with pulmonary emphysema with and without alpha-1 antitrypsin deficiency - Gerard Orriols; Cristina Aljama; Francisco Rodriguez-Frias; Pablo-Gabriel Medina; Roser Ferrer-Costa; Galo Granados; Alexa Nuñez; Ane López-González; Gerardo Ruiz-Satelinas; Marc Miravitlles; Miriam Barrecheguren; Cristina Esquinas (PLoS ONE, 2025)
Pulmonary emphysema, a component of chronic obstructive pulmonary disease (COPD) is characterised by irreversible alveolar tissue destruction and is produced by an imbalance between proteolytic enzymes, mostly neutrophil elastase (NE), and its inhibitors, mainly alpha-1 antitrypsin (AAT). We measured elastase-inhibitory activity (EIA) in serum samples and determined whether there is an association between EIA and COPD severity. This cross-sectional study recruited COPD patients with and without severe alpha-1 antitrypsin deficiency (AATD) and healthy controls. A semi-automated method assessed EIA using a porcine elastase inhibition assay. EIA levels and the EIA/AAT ratio were compared across groups and the correlation with clinical variables was analysed. A total of 86 individuals were recruited: 36 COPD patients, 20 individuals with COPD associated with AATD (Pi*ZZ mutation), of whom 11 were on augmentation therapy, and 30 healthy controls. Positive, linear and significant relationships were observed between EIA and AAT levels. The EIA/AAT ratio was higher in non AATD-related COPD patients compared to untreated Pi*ZZ patients and controls. Further analysis in non-AATD-related COPD patients revealed a higher EIA/AAT ratio associated with older age, higher comorbidity burden and a trend towards higher severity of lung disease. The strong correlation between AAT levels and EIA suggests that the assay technique employed is robust and effective for assessing EIA. The EIA assay may serve as a potential biomarker for the assessment of the severity and prognosis of emphysema.